Proses Politik dalam Pembahasan Ranperda Kota Pekanbaru tentang RPJMD Kota Pekanbaru Tahun 2017-2022 - Rury Febrina; Isril (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2018)
The Regional Medium Term Development Plan (RPJMD) is one of the development planning documents that must be prepared by the regional government 6 months after the regional head is inaugurated. Vision The mission in the RPJMD is the vision and mission of the elected regional head offered to the community at the time of the campaign implementation in the implementation of the Regional Election Committee and adjustments that refer to the existing RPJPD. This means that the RPJMD is a political contract between the regional head and the community during his tenure (5 years). The political process is also interpreted as a stage where there is interaction between the executive and the legislature in the legislative process, especially in relation to the discussion of the RPJMD which sets out the vision and mission of the regional head during his term of office. The legislative process is focused on the stages of discussion and agreement with the DPRD regarding the RPJMD and its relation to the performance of the future regional government.